2004
DOI: 10.1158/0008-5472.can-03-1131
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and the Microenvironment

Abstract: We have investigated the interaction between tumor cells and specific cells in their microenvironment using myeloma as a model. The role of myeloma-induced osteoclastogenesis in the disease was studied ex vivo. Myeloma plasma cells freshly purified from patients' bone marrow attracted committed osteoclast (OC) precursors (n ‫؍‬ 9; P < 0.01) and in 22 experiments directly induced their differentiation to multinucleated, boneresorbing OCs (P < 0.00002) in a receptor activator of nuclear factor-B ligand-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 173 publications
(70 citation statements)
references
References 62 publications
1
69
0
Order By: Relevance
“…Osteoclast Serum-free Co-culture-It has been reported that in co-culture with myeloma cells, osteoclasts support survival and sustained proliferation of freshly purified primary myeloma cells for extended time periods and that this effect requires contact between myeloma cells and osteoclasts (10). Here we present confirmation of these results (Figs.…”
Section: Evaluation Of Cytokines and Chemokines In Myeloma Cell-supporting
confidence: 86%
See 3 more Smart Citations
“…Osteoclast Serum-free Co-culture-It has been reported that in co-culture with myeloma cells, osteoclasts support survival and sustained proliferation of freshly purified primary myeloma cells for extended time periods and that this effect requires contact between myeloma cells and osteoclasts (10). Here we present confirmation of these results (Figs.…”
Section: Evaluation Of Cytokines and Chemokines In Myeloma Cell-supporting
confidence: 86%
“…MM PCs were isolated using CD138 immunomagnetic bead selection and the autoMACs automated separation system (Miltenyi Biotec, Auburn, CA). Purity of MM PC preparations was determined by CD38/CD45 flow cytometry to be routinely 95% (10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These experiments, however, were performed in the absence of the BM microenvironment, known to rescue MM cells from cell death and contribute to the growth of the malignant cells (Pagnucco et al, 2004;Yaccoby et al, 2004;Vincent and Mechti, 2005). To assess the ability of TRAF6C siRNA to interfere with the growth of MM cells within the protective BM microenvironment, 8226/ GFP myeloma cells were transfected with siTRAF6C or siGAPDH and injected into the femoral BM of irradiated mice.…”
Section: Resultsmentioning
confidence: 99%